A hospital-based descriptive study of Ayushman Bharat-Pradhan Mantri Jan-Arogya Yojana: an analysis of 4844 claims - Mufti, Samina; Khalil, Ifrah; Ali, Tuaiba; Mufti, Hammad; Iqbal, Anam; Tariq, Rabbanie; Jan, Farooq A. (International Journal Of Community Medicine And Public Health, 2024)
Background: Current study was undertaken to analyze Ayushman Bharat claims settled during the initial two years of launch of the scheme in an empaneled, public hospital in northern India. Objective was descriptive analysis of 4844 settled claims in terms of demographic characteristics of beneficiaries, procedures and packages availed by them in an empaneled public hospital during the initial two years of the launch of the scheme. Methods: A cross-sectional records study of 4844 settled claims was conducted in a public, empanelled 1015 bedded tertiary care multi-specialty hospital of north India. Anonymized data was collected from the transaction management module of AB-PMJAY scheme and hospitalization record of patients retrieved from medical records department. Results: The study revealed that around 4844 claims were settled during the initial two years (December 2018 to December 2020). Highest number of claims (43.33%) were availed under general medicine category. Chemotherapy packages availed under medical oncology were 37.45% of all claims. Interventional cardiology packages were the costliest. Conclusions: The study provides an insight into the frequency of various claims, their costs, disease/procedural burden of beneficiary patients of AB-PMJAY. It will provide policy feedback and help in future planning and implementation of the scheme.